2006
DOI: 10.2106/jbjs.e.00806
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corticosteroid on Collagen Expression in Injured Rotator Cuff Tendon

Abstract: Background-Subacromial corticosteroid injections are commonly used in the nonoperative management of rotator cuff disease. The effects of corticosteroid injection on injured rotator cuff tendons have not been studied. Our aims were to characterize the acute response of rotator cuff tendons to injury through the analysis of the type-III to type-I collagen expression ratio, a tendon injury marker, and to examine the effects of corticosteroid on this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 46 publications
1
57
1
2
Order By: Relevance
“…The newly formed scar, however, is mainly composed of type III collagen, instead of Col1 and Col2. Galatz et al [2] and Wei et al [56] have demonstrated that the expression of Col1 and Col2 is an important indicator of the total repair outcome of RCT, especially at later stages during repair maturation. In the current study, a significant increase in Col1 and Col2 in the ICA group compared with those in the control group was observed at each time point, while no significant difference was found between ICA and control groups regarding the Col3 protein expression, which indicated the scar tissues cannot be decreased due to the treatment of ICA in early stage (2–4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The newly formed scar, however, is mainly composed of type III collagen, instead of Col1 and Col2. Galatz et al [2] and Wei et al [56] have demonstrated that the expression of Col1 and Col2 is an important indicator of the total repair outcome of RCT, especially at later stages during repair maturation. In the current study, a significant increase in Col1 and Col2 in the ICA group compared with those in the control group was observed at each time point, while no significant difference was found between ICA and control groups regarding the Col3 protein expression, which indicated the scar tissues cannot be decreased due to the treatment of ICA in early stage (2–4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Their side effects are also well documented, such as infection, tendon ruptures, and skin and subcutaneous fat atrophy [9]. In addition, experimental studies suggest that corticosteroids not only damage the ultrastructure of collagen molecules [26] but also inhibit the regenerative properties of tendon stem cells [27]. Surprisingly, this evidence has not prevented the prevalence of injectable corticosteroids in routine management of tendon disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of reduction in collagen type 1 and decorin gene expression appeared to be smaller when corticosteroid treatment was combined with mechanical strain (Chen et al, 2007). Further, a 4.5‐fold increase in the type 3 to 1 collagen expression ratio, a tendon injury marker, in uninjured rat rotator cuff tendons was found 1‐week post‐treatment initiation, which was back to baseline levels by 3 weeks (Wei et al, 2006). Additionally, tendon cell migration, which is fundamental to tendon healing, is delayed by 3 days after corticoid injection in rat Achilles tendons and thereafter the migration is reduced in a dose‐dependent manner (Tsai et al, 2003).…”
Section: Discussionmentioning
confidence: 99%